Inducible clindamycin resistance among clinically significant staphylococcus aureus isolates in a tertiary care centre - SADANANDAN, NISHA (Tropical Journal of Pathology and Microbiology, 2024)
INDUCIBLE CLINDAMYCIN RESISTANCE AMONG CLINICALLY SIGNIFICANT STAPHYLOCOCCUS AUREUS ISOLATES IN A TERTIARY CARE CENTRE ABSTRACT Objective Staphylococcus aureus isolates with inducible clindamycin resistance may lead to therapeutic failure on treating with Clindamycin. Aim: To detect inducible clindamycin resistance of clinically significant Staphylococcus aureus isolates and MIC of clindamycin in them. Study design Crossectional study Study subjects The study was conducted in 200 clinically significant Staphylococcus aureus isolates from Govt medical college, Thrissur Kerala, India over a period of one year Study methods D test was done and iMLSB, cMLSB, MS phenotypes were identified. Epsilometer test was done for determining the MIC of Clindamycin.. Statistical analysis was done using IBM statistical package for social sciences version 25(SPSS). Results Of the total 200 samples 132(66%) were MSSA and 68(34%) were MRSA.MS phenotypes 60(30%), iMLSB phenotype 53(26.5%),cMLSB phenotype 44 (22%), Erythromycin and Clindamycin sensitive strains 41(20.5%) and resistant strains 2 (1%). Inducible and constitutive resistance to clindamycin were more in MRSA.92% of iMLSB phenotypes and 96% of MS phenotypes had MIC < 0.5(sensitive). 8% iMLSB phenotypes and 96% of cMLSB phenotypes had MIC >4(resistant). One isolate with cMLSB phenotype had MIC in intermediate range . Conclusion Prevalence of inducible clindamycin resistance in our hospital is high and more common among MRSA. E test helped to determine MIC in intermediate range (shown by cMLSB phenotype )which is not possible by doing disc diffusion method alone. Most common phenotype isolated was MS phenotype. Keywords iMLSB, cMLSB, MS Phenotype, D test, MRSA, MSSA, MIC